2020
DOI: 10.1002/cncr.33319
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric hepatic cancer incidence and survival: 30‐year trends in Ontario, Canada; the United States; and Australia

Abstract: Background Pediatric hepatic cancer is a rare malignancy, comprising only approximately 2% of all cancers diagnosed in children aged <15 years. The authors sought to describe trends in pediatric hepatic cancer incidence and survival in Ontario, Canada; the United States; and Australia. Methods Children aged <15 years who were diagnosed with hepatic cancer from 1985 through 2013 were ascertained through population‐based registries and followed from the time of diagnosis until December 31, 2015. Age‐standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A study based on the SEER database showed that the 5-year OS rates of HB and HCC were 52.4% and 18.0%, respectively, from 1979 to 1996 ( 2 ). Another study showed that the 5-year OS of CLCa was 68.5% from 1985 to 2013 in the United States ( 17 ). OS rates of CLCa in this study were higher than those in the above studies, which may suggest that the prognosis of CLCa has improved recently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study based on the SEER database showed that the 5-year OS rates of HB and HCC were 52.4% and 18.0%, respectively, from 1979 to 1996 ( 2 ). Another study showed that the 5-year OS of CLCa was 68.5% from 1985 to 2013 in the United States ( 17 ). OS rates of CLCa in this study were higher than those in the above studies, which may suggest that the prognosis of CLCa has improved recently.…”
Section: Discussionmentioning
confidence: 99%
“…OS rates of CLCa in this study were higher than those in the above studies, which may suggest that the prognosis of CLCa has improved recently. Studies have reported that the prognosis of CLCa was closely related to age, year of diagnosis, stage, histopathology type, and therapy ( 17 , 18 ). We performed the penalization procedure using LASSO Cox regression to address overfitting and miscalibration, which has been widely used in medical research ( 19 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mild increase in incidence rates [3] , partly sustained by improving diagnostic techniques, mainly in HIC [4] , [5] , and reduced mortality [6] contribute to growing prevalence. Mortality is decreasing due to the improved survival [1] , [2] , [7] , as seen in Europe [8] , the USA [1] , [9] , Canada, and Australia [9] , [10] . Better survival has been attributed to advances in tumour diagnostics, improved treatment effectiveness, advanced provision and organization of health care, supported by improving socioeconomic conditions, and general health status [8] .…”
Section: Introductionmentioning
confidence: 99%